Tombes et pratiques funéraires protohistoriques des Grands Causses du Gévaudan (Aveyron, Gard, Lozère) - Dedet, Bernard (Documents d'archéologie française, 2001)
This richly illustrated monograph the result of exhaustive documentary research, offers a detailed and standardised critical inventory of Late Bronze Age to fifth century BC funerary assemblages discovered in the Grands Gausses region of France. The work brings together data from excavations carried out since the nineteenth century, presenting a corpus of 240 funerary deposits whose surviving anthropological, faunal and archaeological finds have been completely re-examined. Particular attention is given to the human remains. Seen in relation to hypotheses suggested by historical and ethnological comparisons, this study of funerary practices in the pre-literate world provides insights into organisational structures and social hierarchies, shedding new light on collective notions of death and the after-life.